Electrolyte system strategies for anionic isotachophoresis with electrospray‐ionization mass‐spectrometric detection. 1. Regular isotachophoresis and free‐acid isotachophoresis. Issue 20 (25th September 2013) - Malá, Zdena; Gebauer, Petr; Boček, Petr
<x xml:space="preserve">Abstract</x> The subject of this work is the definition of a simple model based on general ITP theory that allows describing and predicting the behavior of ITP systems compatible with ESI‐MS detection. The model is exemplified by anionic ITP of weak acids that represent an interesting potential application field of ITP‐ESI‐MS. Suitable ESI‐compatible electrolyte systems of very simple composition are proposed including a special free‐acid ITP arrangement. The properties of these systems are discussed using illustrative diagrams of their stacking windows. The use of anionic ITP‐ESI‐MS in negative‐ion ESI mode is reported for the first time and its suitability for sensitive trace analysis is demonstrated. The presented ITP‐ESI‐MS application example comprises a free‐acid ITP system formed of formic and propionic acids and direct injection analysis of ibuprofen and diclofenac in waters with quantitation limits of the order 10−10 M.